Concepções de professores sobre Educação Inclusiva no ensino superior privado - Mauricio Resende Rodovalho; Geraldo Eustáquio Moreira; Djiby Mané (EccoS – Revista Científica)
This article brings up a rather current problem situation, the inclusion of students with special educational needs in Higher Education, since there was a significant increase in the number of places and access to higher education in Brazil since the 1990s. We raised the opinions of the teachers of a Higher Education Institution in the interior of the State of Goiás and analyzed some of their conceptions regarding inclusion, special educational needs and teacher training for inclusion. It is a preliminary study that shows in its results a reality experienced by a small group of teachers that seems to be similar to that experienced by the other teachers of Private Higher Education in Brazil.